Free Vibration Analysis of Clamped Laminated Composite Plates with Centeral Crack - F. Brethee, Khaldoon (Anbar Journal of Engineering Sciences, 2021)
A finite element method for free vibration analysis of generally laminated composite plateswith central crack and clamped edges have been studied using ANSYS 5.4 program. The fiber-reinforced composite materials are ideal for structural applications where highstrength-to-weight and stiffness-to-weight ratios are required, where structures must safelywork during its service life. But damages initiate a breakdown period on the structures.Cracks are among the most encountered damage types in the structures. The non-dimensionalfundamental frequency of vibration decreases with presence of cracks because, therigidity of cracked plate decreases. The natural frequency of plates depends on size andshape of the cracks, the effect of number of layers is found to be insignificant beyond fourlayers and the change of fiber orientation increasing the fundamental frequency of vibration.The results obtained have been compared with the available published literature with goodagreement results